OPTIMALISASI KINERJA KARYAWAN MELALUI PENGELOLAAN STRESS KERJA, BEBAN KERJA, DAN LINGKUNGAN KERJA (STUDI KASUS PADA KARYAWAN BUMN) - M. Rafli Lingga; Wulandari; Ramadan Pasaribu (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to systematically analyze the interaction between work stress, workload, and the work environment, as well as their impact on employee performance within State-Owned Enterprises (SOEs). The primary objective is to determine the extent to which these three variables influence employee performance and how managerial strategies can be effectively implemented to optimize outcomes. A qualitative research method is employed, using an exploratory approach that seeks to gain in-depth understanding of the phenomenon through descriptive data collection. Data for this research were obtained through library research by reviewing various sources, including academic journals, reference books, scholarly articles, and other documents relevant to the themes of work stress, workload, and the work environment. The literature review reveals that these three variables are interrelated and collectively affect employee performance, particularly within the SOE context. Therefore, an integrated approach to managing work stress, workload, and the work environment is essential to enhance employee performance, especially in response to growing job demands.